Why are signals reliable? Honesty depends on costs, sometimes. (December 2015) - Polnaszek, Timothy J.; Stephens, David W.
Highlights: Signal costs can be necessary for honesty, but not in all circumstances. We examine disagreement on key terminology within costly signalling literature. We aim to reconcile differences between 'handicap principle' advocates and critics. Ultimately, 'What maintains honesty?' lies at the heart of costly signalling research.